Droplet-base microfluidics single cell isolation - Choi, Kwok Keong (2015)
Interpretation of DNA profiles is a critical step in the course of criminal investigation. The technical skills involved requires analyst to draw the skills acquired through rigorous training and experience. Arguably, the most challenging DNA profile interpretation are complex mixtures with unknown number of contributors or without reference samples for elimination. Although guidelines were established in the forensics community, the protocols clearly lack robustness and could lead to potential wide range of interpretations. In this study, we seek to resolve samples consisting of cells contributed from more than a single source by individualizing of cells present through the application of droplet microfluidics. Two selected microchip designs were fabricated with soft lithography for isolation of single cells through encapsulation in oil/water emulsion. To achieve this objective, we study and optimized the flow rates and oil:water ratios for operation in the respective microchips. The intend of this study is to spearhead the concept of single cell isolation prior to standard downstream DNA profiling protocols for the purpose of complex mixture resolution.